Análisis de la transformación mecánica y comercialización de madera en el Cantón El Empalme, Provincia del Guayas, año 2018. - Sellán Macías, Elvis Alfredo. (2018)
This research is aimed at: analyzing several aspects related to the processes of mechanical transformation and commercialization of wood of the canton the splice, province of Guayas, identifying the number of existing companies, their spatial distribution in the canton and analyzing the origin of forest products. When you visit the companies and run an interview with owners, it is identified that there are 30 companies in the canton, distributed mainly in the parish Velasco Ibarra that is considered the urban center, dominated by small companies where the monthly marketing volume of wood borders 20 m3. The production chain of forest products starts from the acquisition of wood from the same canton, followed by the Canton Quevedo and caching, being: Teak, white Guayacán and Laurel, the species of highest demand in the local market used for the Elaboration of doors, shelves, canteens and also for the construction sector. Most of the product obtained after sawing teak is destined to the international market, mainly to India. Wood consumption is led by large wooden deposits representing 84.73% of the total consumption of wood, which is equivalent to 4748.10 m3 per month; Sawmills consume 13.66% i.e. 765.78 m3 of wood; The joinery, Bodyworks and mixed establishments are represented with 1.59% consuming a total of 89.46 m3 of wood.